An Insight into the Traditional Uses, Phytoconstituents and Pharmacological Activities of the Genus Tylophora - Satyavarapu Veera Venkata Naga Satya Maha Lakshmi*; Marepally Chandrika; Rebbaniboni Nandin; Mannava Naga Pavithra; Ramadevi Korni; Mohamed Jawed Ahsan (Iranian Society of Pharmacognosy, 2024)
Traditional plants have huge demand as medicines to treat a wide range of illnesses. Tylophora is an important genus of medicinal plant in India, used to treat asthma and other ailments. The plants of this genus have been studied in vivo and in vitro for various pharmacological properties. In this article, we have given information regarding ethnomedicinal importance, phytochemistry and pharmacological uses of 18 species of Tylophora. Comprehensive information regarding different species of Tylophora were collected using different keywords in various electronic databases such as ACS, Google Scholar, PubMed, Science Direct, SciFinder, Web of Science, Springer Link, library search, J gate, Wiley, Semantic Scholar and ResearchGate since 1960 to 2023. Additionally, data was collected from some textbooks and chapters like Flora of India and Indian medicinal plants. This article highlights the traditional uses, phytochemistry, and pharmacological activities of the few studied taxa of Tylophora that would serve as a reference for pharmaceutical research. More than 100 compounds have been isolated from selected species of the genus Tylophora. Among them, phenanthroindolizidine alkaloids have received the most attention and are the most abundant active constituents of the plant. Other types of active components of genus Tylophora include C21 glycosides, secoiridoids, triterpenes, and furano alkaloids. These compounds have shown a variety of therapeutic activities like antiasthmatic, antitumour, antimicrobial, antidiabetic and antiallergic properties. This review can be an important scientific resource for further research.